The dynamic of keitt mango fruit development in the control environment system with respect to time and energy domains - Nurdini Binti Abdul Rani (School of Bioprocess Engineering, University Malaysia Perlis, 2017)
Prediction of time of ripening fruit is crucial to get maximum post-harvest benefit. The quality and productivity of the crop are hard to maintain because the farmers cannot predict the best time to harvest the crop. In order to harvest the Keitt mango at the best time, the ripening stage of Keitt mango has to be established with respect to time or temperature domain. This experiment is design to evaluate the growing time, base temperature and to calculate the value of Growing Degree Day (GDD) of Keitt mango. They are few steps to complete this experiment which is started with setting up the data logger inside and outside greenhouse. After that, the length and width of 5 different fruit of Keitt mango was measured constantly once in a week until it fall. After all fruits are fall, the data logger was taken out. The function of data logger is to record the temperature of surrounding. Finally, the experimental data is analyzed to get the value of base temperature, growing time and value of GDD. The base temperature of Keitt mango is 29C and the value of GDD for Fruit 1, Fruit 2, Fruit 3, Fruit 4 and Fruit 5 is 58.70 GDDs, 71.20 GDDs, 101.20 GDDs, 95.95 GDDs and 87.95 GDDs respectively. The growing time from the middle stage until ripening stage for Fruit 1 is 18 days, Fruit 2 is 23 days, Fruit 3 is 32 days, Fruit 4 is 31 days and Fruit 5 is 29 days